Marketing approaches and problems of small and medium-sized enterprises a case from Turkey - Bakır, Ayşen (My University, 1997)
unknown
Keywords: Genel yönetim; KOBİLER; Pazarlama yönetimi; PAZARLAMA-ŞİRKETLER